2017
DOI: 10.1002/bdr2.1129
|View full text |Cite
|
Sign up to set email alerts
|

Proximity to Pediatric Cardiac Surgical Care among Adolescents with Congenital Heart Defects in 11 New York Counties

Abstract: Background Many individuals with congenital heart defects (CHDs) discontinue cardiac care in adolescence, putting them at risk of adverse health outcomes. Because geographic barriers may contribute to cessation of care, we sought to characterize geographic access to comprehensive cardiac care among adolescents with CHDs. Methods Using a population-based, 11-county surveillance system of CHDs in New York, we characterized proximity to the nearest pediatric cardiac surgical care center among adolescents aged 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…web API, as a new and simple method to conduct similar analyses (Shaw et al, 2017;Sommerhalter et al, 2017). Of particular note is the Google Maps Platform service and its various web APIs (Google Maps APIs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…web API, as a new and simple method to conduct similar analyses (Shaw et al, 2017;Sommerhalter et al, 2017). Of particular note is the Google Maps Platform service and its various web APIs (Google Maps APIs).…”
Section: Resultsmentioning
confidence: 99%
“…By using the Google Maps API, travel times and distances were calculated in consideration of various factors (Google Maps Platform, 2020). In addition, previous studies have used the Google Distance Matrix API, a Google Maps API, to return ETT and ETD results only (Shaw et al, 2017;Sommerhalter et al, 2017). However, our study used the Google Directions API, which provided additional details for directions, in order to confirm whether ferry use was required and thus enabled us to exclude those areas from analysis when needed.…”
Section: Discussionmentioning
confidence: 99%
“…Women in the HSAs surrounding NYC, including the Mid-Hudson and Nassau-Suffolk HSAs, were also more likely to travel farther than their nearest high-level facility for delivery. Previous examinations of travel patterns for CHD patients undergoing surgery showed that 51% of CHD patients who attended a specialty care center traveled farther than the nearest one [28]. While women in both of these areas have a number of appropriate care facilities within close proximity, 41% of women in the Mid-Hudson area who traveled farther to another appropriate care facility delivered at a NYC hospital, compared to only 15% of women in the Nassau-Suffolk area, demonstrating different travel patterns surrounding NYC.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, this study’s methods will be repeated in the future using a known population and distribution of ACHD patients via a registry or other definitive data source. Sommerhalter et al were able to describe true CHD population distribution in an 11‐county area in New York using known addresses of adolescent CHD patients, but expanding their methods to a national scale will be challenging; they were able to link adolescent patients to a statewide birth defects registry, which not all states have, and expanding track‐and‐trace methods to adults adds another layer of complexity …”
Section: Discussionmentioning
confidence: 99%
“…Sommerhalter et al were able to describe true CHD population distribution in an 11-county area in New York using known addresses of adolescent CHD patients, but expanding their methods to a national scale will be challenging; they were able to link adolescent patients to a statewide birth defects registry, which not all states have, and expanding track-and-trace methods to adults adds another layer of complexity. 35 In addition to more accurately describing the true ACHD population, our methodology could be repeated using a different definition of ACHD centers or using board-certified ACHD physicians. As ACHA accreditation continues, using accredited centers in place of mid-to high-volume centers will be a more accurate assessment of access to the specific follow up recommended by the ACC/AHA.…”
Section: Future Directionsmentioning
confidence: 99%